Response of cowpea (Vigna unguiculata L.Walp) accessions to moisture stress - Manneh, N.; Adetimirin, V.O.; Dieng, I.; Ntukidem, S.O.; Fatokun, C.A.; Boukar, O. (MDPI, 2024)
Cowpea is one of the most important leguminous crops in Sub-Saharan Africa (SSA), and moisture stress is among the constraints affecting its productivity. This study was conducted to understand the response of cowpea accessions to moisture stress. A total of 255 cowpea accessions from Togo and four checks from the International Institute of Tropical Agriculture (IITA), were assessed. The trials were conducted in the glasshouse and an open field (which was divided into moisture-stressed (MS) and non-moisture-stressed fields (NMS)). In the non-moisture-stressed environment compared to the moisture-stressed environment, there was a greater heritability for agronomic traits such as biomass, seed weight, and pod weight. The accessions with the highest seed weights (yield-related traits), surpassing the checks under both moisture-stressed and non-moisture-stressed conditions in the field, were six viz.: RK173 (49.8 g (MS); 90.4 g (NMS)), RP225 (34.6 g (MS); 119.9 g (NMS)), RP232 (33.4 g (MS); 51.9 g (NMS)), RM357 (27.9 g (MS); 62.9 g (NMS)), RK148 (23.9 g (MS); 63.4 g (NMS)), and Vu081_2_2 (21.8 g (MS); 46.7 g (NMS)). The most promising accession was RK173; this was ranked first under the moisture-stressed condition and ranked second under the non-moisture-stressed condition with a loss in weight of 44.9% due to drought stress. Of the top 20 accessions that recovered after watering resumed in the glasshouse screening, only the following 9 had a recovery percentage higher than 5% viz.: RS029 (34.5%), RK014 (14.2%), RS114 (9.6%), RK121 (8.3%), RS007 (7.6%), RK123 (7.3%), RS037 (7.3%), RS101 (5.6%), and RS108 (5.1%). The best line and those with a higher recovery percentage could be exploited further in order to improve them in future drought breeding programs by crossing them with lines susceptible to drought or using other drought breeding techniques.